2021
DOI: 10.3390/clinpract11030055
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab-Induced Rhupus Syndrome in a Female Patient Affected with Anti-Citrullinated Protein Antibody (ACPA)-Positive Rheumatoid Arthritis (RA): A Case Report and Review of Literature

Abstract: We report a 38-year-old female patient affected with anti-citrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA) who developed mild hemolytic anemia (Hb = 10.5 vs. >12 gr/dL), indolent oral ulceration, ANA (1:1280, homogeneous pattern), and anti-dsDNA antibody positivity following 8 months of therapy with an adalimumab biosimilar (GP2017). Rhupus syndrome was diagnosed. Replacing GP2017 with infliximab, anemia, oral ulcer, and anti-dsDNA antibodies quickly disappeared, while low-titers (1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[10,14,15] (Table 3). In the same systematic review, 202 of 287 patients were identified with hematological abnormalities, but only a few instances showed autoimmune hemolytic anemia, the majority of which had favorable outcomes [10,[16][17][18][19][20][21][22] (Table 3). Our patient was diagnosed with an overlap between RA and SLE based on clinical signs and symptoms and serological findings, and her illness was complicated by lupus nephritis, autoimmune hemolytic anemia, and CNS vasculitis, which improved following administration of steroids, hydroxyquinone, and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%
“…[10,14,15] (Table 3). In the same systematic review, 202 of 287 patients were identified with hematological abnormalities, but only a few instances showed autoimmune hemolytic anemia, the majority of which had favorable outcomes [10,[16][17][18][19][20][21][22] (Table 3). Our patient was diagnosed with an overlap between RA and SLE based on clinical signs and symptoms and serological findings, and her illness was complicated by lupus nephritis, autoimmune hemolytic anemia, and CNS vasculitis, which improved following administration of steroids, hydroxyquinone, and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 99%